Nonlinear photonics device based on double perovskite oxide Ba2LaTaO6 for ultrafast laser generation. (November 2022) - Guo, Penglai; An, Mingqi; Shu, Yiqing; Peng, Xiaoling; Han, Yueheng; Hu, Haiguo; Chen, Weicheng; Zhao, Yang; Li, Xiaohui; Li, Jianqing
Highlights: Ba2 LaTaO6 saturable absorber is used to ultrafast fiber laser for the first time. Conventional soliton, harmonic mode-locking, three soliton molecule are achieved. An OIM is used to replace the WDM, ISO and OC for flexible integration. Abstract: Using the optical induced deposition, we investigate a saturable absorber (SA) based on tapered fiber and double perovskite oxide Ba2 LaTaO6 for ultrashort pulse fiber laser generation. The Ba2 LaTaO6 is synthesized via a high-temperature solid-state reaction method. The nonlinear optical absorption of the SA is investigated experimentally. Its saturation intensity and modulation depth are 2.66 MW/cm 2 and 24 %, respectively. Depend on intracavity chromatic dispersion management and evanescent field interaction between SA and continuous wave laser, a conventional soliton pulse, a harmonic mode-locking and a three order soliton molecule are also achieved in passively mode-locked fiber laser. This is the first time that double perovskite oxide Ba2 LaTaO6 is applied as a saturable absorber to generate an ultrashort pulse fiber laser with abnormal dispersion regimes. The results prove great potentials of Ba2 LaTaO6 for future research and applications in ultrafast photonics.